Predictors of Client Non-return to Post-intake Counselling - Gold, Joshua M. (Canadian Journal of Counselling and Psychotherapy, 1992)
This study investigated how an analysis of intake information, including psychological symptom status, would discriminate between male and female returners and non-returners to post-intake counselling. The sample consisted of 261 clients (180 women, 81 men) at a university counselling centre. The results revealed distinct psychological symptom statuses and demographic profiles of female and male non-returners to counselling. Implications of these results and directions for future research are discussed.